The Many Worlds of Trauma: An Interdisciplinary Perspective - Calinescu, Amalia (Border Crossing, 2023)
The article presents a multidimensional analysis of trauma. The socio-physiological approach in the first part sets the stage for underlining the role of integrative psychotherapy in addressing traumatic wounds. Drawing from different fields, the study then provides Kazuo Ishiguro’s psychoanalytic approach to understanding the relationship between trauma and human existence, with a particular focus on the interplay between memory, identity and chronic emotional disturbances. The study thus explores how fiction can serve as a therapeutic tool, giving voice to characters who either embark on healing journeys or try to conceal their unhealed wounds within self-contained worlds. Through existential parables, therapeutic fiction can delve into the psychological implications of traumas, offering the possibility of acceptance, or even healing, despite the immutable nature of the past. Ultimately, this interdisciplinary analysis aims to deepen one’s understanding of trauma’s impact on individuals and society while it highlights the potential for healing and growth in real life through the worlds of fiction.